PENGARUH PEMANFAATAN E-LEARNING TERHADAP PENINGKATAN HASIL BELAJAR MAHASISWA SEKOLAH TINGGI PASTORAL DIAN MANDALA GUNUNGSITOLI - Sitepanus Zebua; Rosmala Dewi; Yuniarto Mudjisusatyo; Eka Daryanto (Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this study was to describe the benefits of the e-learning system to students at Sekolah Tinggi Pastoral Dian Mandala Gunungsitoli. This research is a qualitative research with a descriptive approach. The data sources of this research are the students of Sekolah Tinggi Pastoral Dian Mandala Gunungsitoli. Data collection techniques in this study are interviews, observation and documentation studies. The results showed that the effect of (1). the use of e-learning is felt by students with a tendency to shorten time and help economically. (2). The benefits of e-learning are increasingly helping students in terms of good interactions between lecturers and students and between students and students. (3). By utilizing the e-learning system, students are assisted in various information related to lecture materials and references in lectures. (4). With the e-learning system, students no longer only study in the classroom but they can learn outside the classroom, meaning that students are greatly helped for various other activities that support their lectures.